2018
DOI: 10.1021/acs.joc.8b00282
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazolium Naphthoxide Betaine Is a Visible Light Promoted Organic Photoredox Catalyst

Abstract: Benzimidazolium naphthoxide (ONap-BI) was first synthesized and utilized as an unprecedented betaine photoredox catalyst. Photoexcited state of ONap-BI generated by visible light irradiation catalyzes the reductive deiodination as well as desulfonylation reactions in which 1,3-dimethyl-2-phenylbenzimidazoline (Ph-BIH) cooperates with as an electron and hydrogen atom donor. Significant solvent effects on the reaction progress were discovered, and specific solvation toward imidazolium and naphthoxide moieties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 64 publications
0
29
0
1
Order By: Relevance
“…Recently, a zwitterionic visible‐light‐absorbing benzimidazolium naphtholate BINA was successfully employed in photocatalytic deiodination and desulfonylation reactions in the presence of a combined electron and hydrogen atom donor 10 (see Scheme 10). [77] The cationic benzimidazolium moiety can be considered as separated from the naphtholate, since the tilted structure prevents π‐conjugation. The photocatalytic activity was studied using different solvents with attributed Lewis‐basic or Lewis‐acidic characters, as estimated by donor and acceptor numbers.…”
Section: Anionic Compounds As Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a zwitterionic visible‐light‐absorbing benzimidazolium naphtholate BINA was successfully employed in photocatalytic deiodination and desulfonylation reactions in the presence of a combined electron and hydrogen atom donor 10 (see Scheme 10). [77] The cationic benzimidazolium moiety can be considered as separated from the naphtholate, since the tilted structure prevents π‐conjugation. The photocatalytic activity was studied using different solvents with attributed Lewis‐basic or Lewis‐acidic characters, as estimated by donor and acceptor numbers.…”
Section: Anionic Compounds As Photocatalystsmentioning
confidence: 99%
“…Recently,azwitterionic visible-light-absorbing benzimidazolium naphtholate BINA was successfully employed in photocatalytic deiodination and desulfonylation reactions in the presence of ac ombined electron and hydrogen atom donor 10 (see Scheme 10). [77] Thec ationic benzimidazolium moiety can be considered as separated from the naphtholate, since the tilted structure prevents p-conjugation. Thep hotocatalytic activity was studied using different solvents with attributed Lewis-basic or Lewis-acidic characters,a se stimated by donor and acceptor numbers.T he authors concluded that Lewis-basic solvents cause tight interactions with the Lewis-acidic benzimidazolium moiety,w hereas the electronic properties of the Lewis-basic naphtholate anion are less governed, thereby resulting in an increased electrondonating ability.The best results (Scheme 9) were found using DMF as solvent.…”
Section: Naphtholate-catalyzed Dehalogenation and Detosylationmentioning
confidence: 99%
“…As econd controle xperiment in the absence of ( Me PMP Me ) 3 ZrCl showed slow conversion to the dehalogenated product consistent with the observation that BIH derivatives can undergo photochemical reactions in the absence of photosensitizers. [87,88] However, the reduced rate of conversionc learly shows that ( Me PMP Me ) 3 ZrCl acts as ap hotosensitizer in this transformation.…”
Section: Photoredox Catalysismentioning
confidence: 99%
“…Additional experimental validation was provided by performing nanosecond time-resolved spectroscopy (transient absorption spectra;F igure 5a). [27,28] detectable evidence of al ong-lived transient species (Figure 5b). Thel ifetime of the transient species of 1 was markedly shortened under air (t = 0.15 ms), indicating that it was at riplet species (Supporting Information, Figure S7).…”
Section: Resultsmentioning
confidence: 99%